The Determination of Opinions of Triathlon Athletes on Doping and Anti-Doping Matters - Cemal, Gundogdu; Evrim, Celebi; Beyazcicek, Ozge; Beyazcicek, Ersin; Sakir, Tufekci; Recep, Ozmerdivenli (Duzce Univ, 2017)
Objectives: This study aims to determine the knowledge of triathlon athletes on the types of doping used in sports as well as their opinions on the anti-doping matters. Methods: This descriptive study was conducted with 92 individuals participated in Tasucu Triathlon and Istanbul Salcano Triathlon Series, which was organized in 2015 by the Turkish Triathlon Federation. A questionnaire was used to collect data. Chi-square test was used in analysis of the data. Corticosteroids, masking agents, anti-estrogenic agents, beta blockers, and cannabinoids were among the types of doping which were least known by the triathlon athletes. These were followed by peptide hormones, narcotic analgesics, anabolic-androgenic steroids and stimulants. Results: Approximately two thirds of triathlon athletes consider that knowledge of athletes, coaches and administrators on doping is not sufficient. Conclusion: The majority of the athletes participated in the study stated that the relevant institutions and organizations are not fighting against doping adequately.
Keywords: Triathlon; Triathletes; Doping; Anti-Doping